1999
DOI: 10.1016/s0014-2921(98)00027-0
|View full text |Cite
|
Sign up to set email alerts
|

Technology, resource endowments and international competitiveness

Abstract: This paper attempts to evaluate the role of technology in combination with resource endowments and economies of scale as determinants of industrial patterns of comparative advantage, international competitiveness and specialization within manufacturing among OECD countries. Thus we attempt to combine two paradigms from trade theory, namely the technology or Ricardian view, and the factor proportions or Heckscher-Ohlin explanations of changes in trade patterns.Within the large empirical literature on the determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…In most cases, however, it is reasonable to believe that spillover effects to other firms and other industries are also important. Gustavsson et al (1999) find empirical evidence of both domestic within-industry and economy-wide spillovers, and indications of global spillovers between open economies. Thus, ecoinnovations are characterised by a double externality problem.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In most cases, however, it is reasonable to believe that spillover effects to other firms and other industries are also important. Gustavsson et al (1999) find empirical evidence of both domestic within-industry and economy-wide spillovers, and indications of global spillovers between open economies. Thus, ecoinnovations are characterised by a double externality problem.…”
Section: Introductionmentioning
confidence: 90%
“…There are several sources of ITC (see e.g. Gustavsson et al 1999). The most important ones are probably learning by doing and R&D activity.…”
Section: Introductionmentioning
confidence: 99%
“…This can explain why recyclers in developing countries depending on imports for their inputs generally operate more efficiently than recyclers depending on domestic resources. Gustavsson et al (1999) find that R&D activity at the firm level is particularly advantageous in large and growing economies, where local positive externalities and spillovers magnify the benefits. R&D is especially of vital interest to high and medium technology sectors.…”
Section: Trade Theories Involving Technical Change and Capabilitiesmentioning
confidence: 90%
“…Also, Tsang et al (2008) concluded that value-added generated by R&D is greater in high-tech industries than in low-tech. Moreover, Gustavsson et al (1999) and Kafouros (2005) found that the impact of R&D investment on competitiveness and productivity is significant for hightech industries, but it is low for the traditional manufacturing sector.…”
Section: Role Of Randd Investment On Operational Performancementioning
confidence: 99%